2010
DOI: 10.1111/j.1476-5381.2010.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of CYP2C8 and CYP3A4 in the N‐demethylation of imatinib in human hepatic microsomes

Abstract: BACKGROUND AND PURPOSEImatinib is a clinically important inhibitor of tyrosine kinases that are dysregulated in chronic myelogenous leukaemia and gastrointestinal stromal tumours. Inter-individual variation in imatinib pharmacokinetics is extensive, and influences drug safety and efficacy. Hepatic cytochrome P450 (CYP) 3A4 has been implicated in imatinib N-demethylation, but the clearance of imatinib decreases during prolonged therapy. CYP3A phenotype correlates with imatinib clearance at the commencement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 37 publications
(55 reference statements)
3
69
0
Order By: Relevance
“…However, we cannot exclude an additional influence of imatinib. As a potent CYP3A4 inhibitor, imatinib could theoretically increase the exposure to vincristine and dexamethasone, both of which are metabolized by the enzyme (Duckett & Cameron, 2010;Green et al, 2010;Nebot et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude an additional influence of imatinib. As a potent CYP3A4 inhibitor, imatinib could theoretically increase the exposure to vincristine and dexamethasone, both of which are metabolized by the enzyme (Duckett & Cameron, 2010;Green et al, 2010;Nebot et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…C.5; Suttle et al, 2015). Imatinib, the first tyrosine kinase inhibitor approved for clinical use, is metabolized by several CYP enzymes in vitro, with CYP2C8 and CYP3A4 being the most important ones (Nebot et al, 2010;Filppula et al, 2013a). CYP3A4 is involved in several metabolic pathways of imatinib, whereas CYP2C8 only catalyzes the formation of the main metabolite, N-demethylimatinib (Table 4; Rochat et al, 2008;Filppula et al, 2013a).…”
Section: A Drugsmentioning
confidence: 99%
“…eu/docs/en_GB/document_library/EPAR_-_Product_Information/human/ 000406/WC500022207.pdf, http://www.accessdata.fda.gov/drugsatfda_ docs/nda/2001/21335_Gleevec.cfm) (Rochat et al, 2008;Nebot et al, 2010). Recently, however, we demonstrated that imatinib is a potent mechanism-based inhibitor of this enzyme in vitro, and clinically relevant imatinib concentrations were predicted to cause up to 90% inhibition of hepatic CYP3A4 activity (Filppula et al, 2012).…”
Section: Introductionmentioning
confidence: 99%